Identity, legitimacy and “making sense” of police use of force - Bradford, B; Milani, J; Jackson, J (Emerald, 2017)
Purpose The purpose of this paper is to examine the extent to which police legitimacy and social identity explain variation in public acceptance of police use of force. The authors assess whether there is an association between legitimacy and public acceptance of apparently illegal or unethical police action; and the extent to which identification with a particular social group predicts judgments of police behavior. Design/methodology/approach The study draws upon cross-sectional data from a 2015 survey of a representative sample of adults in England and Wales. Structural equation modeling is used to model conditional correlations between latent constructs. Findings There are two main findings. First, identifying more strongly with a social group that the police may be seen to represent was consistently associated with greater acceptance of police use of force, whether or not that force seemed to be justified. Second, beliefs about the legitimacy of the police were also associated with acceptance, but primarily only in relation to the use of force in situations where it appeared prima facie justifiable. Social implications Results suggest one possible set of reasons why police retain public support in the face of scandals concerning excessive use of force. Originality/value This is one of only very few studies that have used survey data to explore lay justifications for police use of force.